Minimally Oxidized-LDL-Driven Alterations in the Level of Pathological Mediators and Biological Processes in Carotid Atherosclerosis - Thankam, Finosh G; Rai, Taj; Liu, Jeffrey; Tam, Jonathan; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2022)
The global burden of cerebrovascular disease, especially cerebral infarction has been increasing at an alarming rate with the atherosclerosis in carotid arteries as the primary risk factor. Despite the active involvement of minimally oxidized LDL (oxLDL) in atherosclerosis, limited information is available regarding the role of oxLDL in the pathogenesis of cerebrovascular diseases. The present study utilized the carotid bifurcation tissues and isolated carotid SMCs challenged with oxLDL from clinically relevant minimally invasive minimally-oxLDL-induced carotid atheroma microswine model to examine the levels of pro-atherogenic and pro-inflammatory mediators and cellular processes following immunostaining approaches. The immunopositivity of IL18, PDGFRA, IL17, LOX1, TLR4, MYF5, IL1B, and PDPN were increased in the carotid artery bifurcation tissues with a concomitant decrease in DAMPs, HMGB1 and S100B in oxLDL (600μg)-treated group compared to non-intervention control. Moreover, the cultured SMCs displayed increased level of IL18, LOX1, TLR4, MYF5, NLRP3, and PDPN upon challenging with oxLDL (100 mg/ml) compared to non-treatment control. In addition, the SMCs treated with oxLDL were resistant to the peroxidation of lipids as evident from lipid peroxidation staining. Also, the oxLDL displayed compromised mitochondrial membrane potential based on mitochondrial pore transition assay and increased hypertrophy due to decreased level of microtubules. Overall, oxLDL alters the expression status of pathological mediators and multiple biological processes in carotid SMCs aggravating carotid atherosclerosis. The understanding regarding the molecular mechanisms underlying oxLDL-driven pathological events would open novel translational avenues in the management of carotid atherosclerosis.